2021
DOI: 10.3390/en14102937
|View full text |Cite
|
Sign up to set email alerts
|

Refining and Reuse of Waste Lube Oil in SI Engines: A Novel Approach for a Sustainable Environment

Abstract: The protection of the environment and pollution control are issues of paramount importance. Researchers today are engrossed in mitigating the harmful impacts of petroleum waste on the environment. Lubricating oils, which are essential for the smooth operation of engines, are often disposed of improperly after completing their life. In the experimental work presented in this paper, deteriorated engine oil was regenerated using the acid treatment method and was reused in the engine. The comparison of the propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Moreover, an extensive study is available about the refining and re-deployment of the waste lube oil regarding SI engines. The novel study explained the impact of various conditions of lubricating oil on engine characteristics [10]. In another related study, it was found that the moisture level in the lubrication oil was higher for ethanol at 85% concentration in gasoline than simple gasoline in SI engines [11].…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, an extensive study is available about the refining and re-deployment of the waste lube oil regarding SI engines. The novel study explained the impact of various conditions of lubricating oil on engine characteristics [10]. In another related study, it was found that the moisture level in the lubrication oil was higher for ethanol at 85% concentration in gasoline than simple gasoline in SI engines [11].…”
Section: Introductionmentioning
confidence: 93%
“…Nowadays, researchers are focused on quantifying the adverse environmental effects of ULOs [2]. It is of particular concern that, the RESEARCH products of ULO burning generate environmental pollutants that over time, also pollute other places than those close to the ULO generation sites [3].…”
Section: Introductionmentioning
confidence: 99%
“…When operating HCPV systems, keeping the solar cells cool is one of the most important aspects [7]. When triple-junction solar cells receive large amounts of solar intensity, they heat up, and as the temperature increases, the efficiency and power output of the cells lower.…”
Section: Introductionmentioning
confidence: 99%